PERAN INTERNATIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENGATASI MASALAH KEMANUSIAAN DI ACEH TAHUN 2004-2006 - Hany Rafika; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research is analysing about the role of International Committee Red Cross (ICRC) to implementating Humanitarian Law beside it jobs to address the crisis that occured because of civil conflict or nature disaster in Aceh, Indonesia. Conflict in Aceh involving the Freedom Movement of Aceh (GAM).The ICRC is an impartial humanitarian organization, neutral and has a mission to protect the lives and dignity of victims of armed conflict, war and other situations of violence and provide aid and assistance in the form of materials or services. ICRC served in four types of situations such as: International Amed Conflict, Non-international Armed Conflict, Internal Disturbance, and Internal Tension.Humanitarian crisis that occurred in Aceh is a Freedom Aceh Movement (GAM) armed conflict and the tsunami disaster.GAM is a form of rebellion undertaken by the people of Aceh who want to be independent and irrespective of the State of Indonesia. The desire is triggered by a mismatch between the Acehnese people who tend to wear Islamic Sharia law and the Indonesian government tends to neo-colonial.Tsunami is the largest natural disasters in history. Begins with an earthquake measuring 9.1 to 9.3 on the Richter scale lasted 8-10 minutes and produce large waves and a deadly attack by 14 countries and killed as many as 230,000 people. This study discusses how the role of the ICRC in overcoming the crisis of natural disasters that occurred in the Aceh.Keywords: International Committee of The Red Cross, Aceh, Role, Humanitarian Crisis